Salvaging happiness a comprehensive design project - Rusiana, Dominik G.; Espina, Cristopher P. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The Bataan Nuclear Power Plant was made in 1981 to augment the energy supply in Luzon, Although completed it never commenced energy production due to the controversies surrounding the plant. It is located in Morong, Bataan, which is a 2hr drive from Manila situated on top of a flat peninsula perched on a cliff along the Morong coastline, costing the national government 27 million annually to maintain, the plant is seen as a white elephant by many. Thus the problem is how to increase tourist arrivals in Morong, Bataan while making use of the Bataan Power Plant? By utilizing the power plant for revenue generation, the project can defer the cost of maintenance. Thus the following are my design strategies
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Tourism; Tourism -- Morong -- Bataan -- Philippines